Personality Traits of the Regional People's Representative Council (DPRD) of North Kalimantan Province in the Formation of Regional Legal Products - Pandi, Mohammad; Ibrahim, Muh. Akmal; Haning, Thahir; Yunus, Muhammad (Journal of Management and Administration Provision, 2024)
The legislative function of the Regional People's Representative Council (DPRD) can be seen in how regional legal products are formed. This study aims to analyze the personality traits of the DPRD of North Kalimantan Province for the 2019-2024 period in the formation of regional legal products. This study uses a qualitative research method. Data collection methods include observation, interviews, and documentation. Data sources consist of primary and secondary data. The data analysis technique used is an interactive analysis model. Meanwhile, the informants in this study are the authorized parties and those directly involved in forming regional legal products in the North Kalimantan DPRD for the 2019-2024 period. The results of the study show that the personality traits of the Regional People's Representative Council (DPRD) of North Kalimantan Province in the formation of regional legal products have not been effective. This is because the DPRD of North Kalimantan Province for the 2019-2024 Period has not shown facilitative leadership, DPRD initiatives are still lacking, the attitude of DPRD members sometimes ignores the agreed schedule and their knowledge, level of education and capacity are still limited in the formation of regional legal products.